Employee Generated Content, Brand Awareness, and Purchase Intention: An Analysis of Skintific’s TikTok Presence - Raditya Kautsar; Sampurno Wibowo; Alma Syifa (Lembaga Teewan Journal Solutions, 2026)
The increasing competition in the beauty industry on TikTok has encouraged companies to utilize Employee-Generated Content (EGC) as an authentic communication strategy to enhance Brand Awareness and consumers' Purchase Intention. This study aims to examine the influence of Employee-Generated Content (EGC) and Brand Awareness on Purchase Intention toward Skintific products on TikTok. This study employed a quantitative approach using a purposive sampling technique involving 101 TikTok users in Bandung City, Indonesia. Data were collected through a five-point Likert scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings indicate that both Employee-Generated Content and Brand Awareness have a positive and significant effect on Purchase Intention, both partially and simultaneously. Employee-Generated Content demonstrates a more dominant influence than Brand Awareness. Furthermore, these two variables explain 70.2% of the variance in Purchase Intention. The findings highlight that authentic content created by employees plays a crucial role in strengthening brand awareness and encouraging consumers' purchase intention toward Skintific products on TikTok. This study contributes to the digital marketing literature by providing empirical evidence on the effectiveness of Employee-Generated Content as a credible communication strategy in the beauty industry.